Monitoring for overreaching in rugby league players - Coutts, A. J.; Reaburn, P.; Piva, T. J.; Rowsell, G. J. (European Journal of Applied Physiology, 2007)
The aim of this study was to identify indicators of non-functional overreaching (NFOR) in team sport athletes undertaking intensive training loads. Eighteen semi-professional rugby league players were randomly assigned into two pair matched groups. One group completed 6 weeks of normal training (NT) whilst the other group was deliberately overreached through intensified training (IT). Both groups then completed the same 7-day stepwise training load reduction taper. Multistage fitness test (MSFT) performance, peak aerobic running velocity (V max), maximal heart rate, vertical jump, 10-s cycle sprint performance and body mass were measured pre- and post-training period and following the taper. Hormonal, haematological and immunological parameters were also measured pre-training and following weeks 2, 4 and 6 of training and post-taper. MANOVA for repeated measures with contrast analysis indicated that MSFT performance and 'were significantly reduced in the IT group over time and condition, indicating that a state of overreaching was attained. However, the only biochemical measure that was significantly different between the IT and NT group was the glutamine to glutamate (Gln/Glu) ratio even though testosterone, testosterone to cortisol (T/C) ratio, plasma glutamate, and CK activity were significantly changed after training in both groups. Positive endurance and power performance changes were observed post-taper in the IT group confirming NFOR. These changes were associated with increases in the T/C ratio and the Gln/Glu ratio and decreases in plasma glutamate and CK activity. These results indicate that although there was no single reliable biochemical marker of NFOR in these athletes, the Gln/Glu ratio and MSFT test may be useful measures for monitoring responses to IT in team sport athletes.